The impact of digitalization on employmentproductivity and the role of Social Protection: Socio-economic costs andlegal options - Tsetoura, Anna (Social Cohesion and Development, 2024)
The paper begins with a description of digitalization of work. The negative effects are the first to be examined and subsequently the positive effects are presented. Five outcomes with double effects (a negative and a positive one) arise from the analysis of digitalization on employment and productivity. Further, the implications of digital work on social security are illustrated, as well as the legal lacunae at a national, European and international level. Lastly, we conclude to suggestions which could counterbalance the negative effects and enhance the positive ones utilizing techniques from the European legal order.